Critical thinking for higher education: Are our students ready? - Ngeow, Y.M. (2014)
How can we improve, the quality of undergraduate learning by instilling critical thinking while focusing on learning how to learn? Can critical thinking be learnt via students self-directed learning? My curiousity on this matter prompted me to conduct this teaching inquiry, Despite the urgent need to stimulate critical thinking skills among students, are they willing to learn and ready to use these skills in my course? I conducted inquiry on eight first-year students who in general demonstrated relatively higher level of thinking skills in individual critical essays. Resulting from this inquiry, my paper looks into two aspects of learning critical thinking: (I) How did students learn to acquire critical thinking skills prior to their tertiary education? (2) How would do students perceive thinking skills during their university life') By reflecting on students' learning experience, needs and aspirations, I hope they have their voices heard by concerned educators, As the major stakeholders in whatever innovative educational reforms, students need to be given opportunity to speak up, This shall be an evidence of student-centered learning, and respect for young minds is salute to critical thinking,